The reasons which secondary education students are heading to private tutoring from the parents’ opinions (Field Study in Lattakia City) - غانم ثناء; زمرد أميرة; حسن باسل (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aims to find out the reasons which secondary education students are heading to private tutoring from the parents’ opinions, and investigated the differences in their opinions on that according to the variables (the guardian’s gender "male – female" – the son’s academic specialization "scientific – literary"). The researcher used the descriptive approach, and the tool was a questionnaire prepared by the researcher and studied the characteristics of the sciences, consisting of (42) items divided into (4) axes, which are (reasons belonging to the student – curriculum – teacher – school and the school system). Applying the questionnaire to (377) parents of secondary education students in lattakia. The results of the research showed that the student’s desire to obtain high grades, better information by the teacher and richer information during the private tutoring, and the student’s ability to choose the teaching staff he wants, in addition to the student’s preference for the teaching method followed in the private tutoring came at the forefront of the reasons for the orientation of the students of the stage. Secondary from the parents’ opinion towards private tutoring, Whereas the following reasons are the difficulty and magnitude of some curricula, the weakness of some teachers ’motivation to teach well in the classroom, the density of the classroom number of students, as well as the poor professional preparation of some teachers, as the lowest reasons for the orientation of high school students from the opinion of parents towards private tutoring, In general, the reasons for students ’enrollment in private tutoring were on the questionnaire as a whole with a moderate degree, as well as the absence of a statistically significant relationship at the level of (0.05) between the monthly income of the family and the students’ orientation towards private tutoring, and the results showed that (296 of the sample members chose to answer "yes" to the question related to whether their son / daughter has received private tutoring, and that (94.5%) of them reported that their son / daughter received private tutoring in at least three subjects. Based on the results obtained, it is evident that studies should be conducted on the prevalence of private tutoring in the various educational stages in the absence of accurate statistics about their prevalence, and to address the various parties related to the topic of research (students, teachers, professional mentors and others), and the need to tighten control over the process Teaching centers in schools on the one hand, and educational centers (institutes) on the other hand.